Early Marriage and Reproductive Immunology: A Critical Literature Review - Pauzan Pauzan (Jurnal Biologi Tropis, 2026)
Early marriage is a reproductive health issue associated with an increased risk of maternal complications and reproductive immune system disorders in adolescent females. The immaturity of reproductive organs and the immune system at a young age increases susceptibility to infections, anemia, preeclampsia, and preterm birth. This article aims to examine the relationship between early marriage and reproductive immune dysregulation from the perspective of reproductive immunology. The method used was a systematic literature review through the analysis of various scientific publications related to reproductive health, adolescent pregnancy complications, and immune responses. The findings indicate that early marriage is associated with disturbances in both innate and adaptive immunity, including alterations in the activity of T cells, B cells, macrophages, and natural killer cells, which play essential roles in maintaining immunological tolerance during pregnancy. This immune dysregulation increases the risk of sexually transmitted infections, obstetric complications, and impaired fetal and neonatal growth. Furthermore, malnutrition and psychosocial stress among adolescents may further worsen immune function and maternal health. Therefore, early marriage represents an important risk factor for reproductive immune disorders and maternal-child health problems.